Mechanism of action and the effect of Beta-Hydroxy-Beta-Methylbutyrate (HMB) supplementation on different types of physical performance - A systematic review - Kaczka, P.; Magdalena, M.; Jastrzab, R.; Gawelczyk, M.; Kubicka, K. (Journal of Human Kinetics, 2019)
Beta-hydroxy-beta-methylbutyrate (HMB) has been used extensively as a dietary supplement for athletes and physically active people. HMB is a leucine metabolite, which is one of three branched chain amino acids. HMB plays multiple roles in the human body of which most important ones include protein metabolism, insulin activity and skeletal muscle hypertrophy. The ergogenic effects of HMB supplementation are related to the enhancement of sarcolemma integrity, inhibition of protein degradation (ubiquitin pathway), decreased cell apoptosis, increased protein synthesis (mTOR pathway), stimulation of the growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis and enhancement of muscle stem cells proliferation and differentiation. HMB supplementation has been carried out with various groups of athletes. In endurance and martial arts athletes, HMB supplementation revealed positive effects on specific aerobic capacity variables. Positive results were also disclosed in resistance trained athletes, where changes in strength, body fat and muscle mass as well as anaerobic performance and power output were observed. The purpose of this review was to present the main mechanisms of HMB action, especially related to muscle protein synthesis and degradation, and ergogenic effects on different types of sports and physical activities.